MIMO STC 2x2 MODEL BASED On WiMAX 802.16e-2005 STANDARD - WAHYU ARDIANSYAH (NIM 13204215), ANDJAS
This final project describes designing and simulating MIMO STC 2x2 based on WiMAX 802.16e-2005 Standard. Model also must fullfil specification of WiMAX Forum Wave-2 System Profile. This model will be used as reference for WiMAX Wave-2 hardware (chip) design. MIMO STC model needs two subsistem, MIMO STC transmitter subsistem and MIMO STC receiver subsistem. First, MIMO STC transmitter subsistem which is consist of MIMO switch, STC decoder dan MIMO subcarrier mapper. Second, MIMO STC transmitter subsistem which is consist of MIMO subcarrier demapper, MIMO channel estimator, dan STC decoder. Simulation shows the performance of designed model BER Vs SNR has fullfil the minimum perfomance requirement of the Standard. The same BER performance was achieved at SNR 4-9 dB lower than standar requirement. Designed model also exceeds performance of a system with similar specification on the literature. Our model performance had SNR 10-12 dB lower than literature. This is because our model only uses the bit precision process (quantization process from decimal to binery) only in demodulation and channel decoding. Also noted, Performance of model with Lagrange-2 interpolation is better than model with linear estimation. This is because; real channel response which is in form of nonlinear curve so Lagrange-2 interpolation could estimate better than linear interpolation. Final conclusion, our model has fullfil the requirement to be used as reference in hardware design.